Level of satisfaction of students of the bachelor’s degree in nursing regarding clinical simulation - Montijo-Arriola, Ana Lucia (Universidad de Sonora, 2020)
Introduction: Nursing, as a theoretical-practical profession, may be visualized from the sociocultural constructivist perspective, where the student constantly acquires and generates new knowledge, in particular, after interventions with clinical simulators. Objective: To identify the level of satisfaction of students in the Bachelor’s Degree in Nursing before clinical simulation in the laboratories of a public university of northwestern Mexico. Methodology: Quantitative and correlational study, at random sampling, and stratified probabilistic sample of 149 students per semester. The socio-demographic data card and the Questionnaire of Quality and Satisfaction of the Clinical Simulation Classroom from the University of Cantabria were used, using Cronbach’s Alpha of .912. Results: The mean age of participants was 20.66 years, in terms of sex 75.2% (f = 112) corresponded to female students. The average satisfaction with the use of the clinical simulation laboratory was 81.52. The variables of semester in which the student is enrolled (p=.000) and that the student is engaged in a remunerated activity (p=.041) have a statistically significant relationship to the level of satisfaction. Conclusions: Data obtained showed that the students are very satisfied with the clinical simulation.